Post-Transplant Vitamin D Deficiency in Lung Transplant Recipients: Impact on Outcomes and Prognosis - Min Seo Ki; Min Seo Ki; Nam Eun Kim; Ala Woo; Song Yee Kim; Young Sam Kim; Ha Eun Kim; Jin Gu Lee; Hyo Chae Paik; Hyo Chae Paik; Moo Suk Park (Transplant International, 2024)
Despite the recognized clinical significance of vitamin D deficiency in other solid organ transplant recipients, its specific relevance in lung transplantation remains to be fully understood. In this study, we performed a retrospective observational study on the impact of vitamin D deficiency on clinical outcomes and prognosis in 125 lung transplant recipients (LTRs) from October 2014 to March 2020 at a university hospital in Seoul, South Korea. Among 125 LTRs, 51 patients (40.8%) were vitamin D deficient. LTRs in the vitamin D-deficient group exhibited a higher incidence of post-transplant pneumonia and overall mortality than those with normal vitamin D levels during the follow-up period. This trend persisted when subjects were stratified into vitamin D tertiles. Furthermore, post-transplant vitamin D levels and C-reactive protein (CRP) significantly impacted pneumonia incidence and survival outcomes. Prognosis also varied based on cumulative vitamin D supplementation after transplantation, with patients receiving higher cumulative supplementation demonstrating improved prognosis. Our findings underscore the importance of assessing and maintaining optimal vitamin D levels post-transplantation, suggesting a potential avenue for improving outcomes in lung transplant recipients, especially in mitigating infection risk and enhancing long-term survival. Further research into optimal vitamin D levels and supplementation strategies in this population is warranted.